2016
DOI: 10.1021/acsami.6b05200
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Peptide–TiO2 Interfaces: Isoenergetic Binding via Either Entropically or Enthalpically Driven Mechanisms

Abstract: A major barrier to the systematic improvement of biomimetic peptide-mediated strategies for the controlled growth of inorganic nanomaterials in environmentally benign conditions lies in the lack of clear conceptual connections between the sequence of the peptide and its surface binding affinity, with binding being facilitated by non-covalent interactions. Peptide conformation, both in the adsorbed and non-adsorbed state, is the key relationship that connects peptide-materials binding with peptide sequence. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 72 publications
5
58
0
Order By: Relevance
“…We identified the range of values of ℎ ℎ and based on our previous work. 3,[5][6][7]33 The range of values between ℎ ℎ and represents an uncertainty band for which we suggest that the outcomes cannot be predicted with confidence. Figure 8 also highlights the four systems with the most inconsistency in terms of the NP stabilization assay, where the degree of confidence in our predictions is low.…”
Section: Au Nanoparticle Synthesis and Characterization Figures 4a Amentioning
confidence: 99%
“…We identified the range of values of ℎ ℎ and based on our previous work. 3,[5][6][7]33 The range of values between ℎ ℎ and represents an uncertainty band for which we suggest that the outcomes cannot be predicted with confidence. Figure 8 also highlights the four systems with the most inconsistency in terms of the NP stabilization assay, where the degree of confidence in our predictions is low.…”
Section: Au Nanoparticle Synthesis and Characterization Figures 4a Amentioning
confidence: 99%
“…The binding specificity was largely due to the hydrophobic interactions between alanine (A) and leucine (L) residues of the peptide and the methyl and methine groups of the PLLA. Sultan et al [11] demonstrated that the binding of peptides to the solid surface was mediated by the ionic strength of the solvents, which further determined the nature and structure of the adsorbed peptide layer. Quartz crystal microbalance with dissipation monitoring (QCM-D) analysis performed on two distinct titanium (Ti)-binding peptides of different overall charge and hydrophobic residues showed that while water as the solvent leads to the formation of viscoelastic multilayers on the surface, a 0.15 M NaCl saline solution directed the formation of a rigid monolayer on the surface for both the peptides studied.…”
Section: Introductionmentioning
confidence: 99%
“…The binding free energy is ∆F ads = 12.1 kJ mol −1 from Equation (5) (or 17.2 kJ mol −1 via Equation (6)). CMD simulations have reported similar values of the binding free energy when the COO − -group is in direct contact to the surface [58] and via surface hydroxyls [59]. A water-mediated adsorption mode has not been found due to the weak nature of this interaction in classical models.…”
Section: Tight-binding Resultsmentioning
confidence: 93%